An Empirical Study for the Correlation Between Disclosed Related Party Transactions and the Market Value of Companies Listed on the Amman Stock Exchange - Hisham Mohammed Ahmed Al-Shayeb; Tawfiq H. Abdel-Jalil (Journal of Corporate Governance Research, 2024)
This study examines the correlation between related parties’ transactions (RPT) and company’s market value in Jordan. In this study the related party transactions were covered through operationalized into three forms that are: Transactions with parent company, subsidiaries and affiliated companies (TPSAC), Transactions with associated companies (TAC) and Transactions with main shareholders, directors and/or managers (TMSDM), in order to see the impact on company’s value. This study considered all the companies listed in Amman Stock Exchange (ASE) at the end of year 2018 with total number of 226 companies for all sectors. After excluding companies with missing data, the final sample size was 218 companies; covering almost 96% of population. Multiple regression test was used to examine the study’s hypotheses. The result of the study indicates that the related party transactions (RPT) Shown a positive effect on (TQ) which represents the company’s value with presence of the control variables (audited by one of the big four audit firms (BIG), size of the company (SIZE), return on assets (ROA), and dividend yield (DIV). The results also show the increasing influence of the independent variable on the dependent variable with presence of the control variables.